Self-supporting ruthenium-copper alloy nano material and application thereof in preparation of amino compound through electro-catalysis

By adopting the self -supporting RUCU NSS material (RUCU NSS), the problem of poor stability and low response rate in the process of electrical catalytic nitrite germination is solved, and high -efficiency and stable electrocatalytic reduction is suitable for industrial production.

CN119352076AActive Publication Date: 2025-01-24NANJING UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411468841.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-21
Publication Date
2025-01-24
Estimated Expiration
2044-10-21

AI Technical Summary

Technical Problem

The prior art has problems such as poor stability, low reaction rate, low tolerance to reaction conditions and poor matrix expansion when electrocatalyzed reduction of nitroaromatic hydrocarbons to aryl amines, which limits its widespread use in industrial applications.

Method used

The self -supported copper alloy nanomaterials (RUCU NSS), through specific synthetic steps, include washing hydrochloride, soaking of excessive sulfate and alkaline solution, soaking in chloride solution, heating treatment and electrochemical reduction to prepare efficient catalysts.

Benefits of technology

RuCu NSs achieves ultra-high yield, Faradaic efficiency and selectivity under a wide range of potential, pH value and substrate concentration conditions. It can operate stably for 1060 hours and obtain kilogram-level products, showing good application potential.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119352076A_ABST
    Figure CN119352076A_ABST
Patent Text Reader

Abstract

The invention provides a self-supporting ruthenium-copper alloy nano material which is prepared by the following steps: soaking foamy copper cleaned by hydrochloric acid in an ammonium persulfate and potassium hydroxide solution, then washing the foamy copper with deionized water, soaking the foamy copper in a ruthenium chloride solution, heating the foamy copper to 200 DEG C under the protection of inert gas, maintaining the temperature for 2 hours, and then cooling the foamy copper to room temperature, thereby obtaining the self-supporting ruthenium-copper alloy nano material. And finally, reducing in a 1M KOH solution at the current density of-100mAcm <-2 > for 6 hours to obtain the product. The self-supporting RuCu catalyst is synthesized by adopting an ultrafast and simple ion exchange method, nitro-aromatic hydrocarbon can be efficiently electrically reduced into arylamine, and super-high yield, Faraday efficiency and selectivity can be realized in a very wide potential range. In a wide pH value solution range and a wide nitrate concentration range, high performance can be maintained, and good application potential is shown.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an electrocatalytic catalyst, in particular to a self-supporting ruthenium-copper alloy nanomaterial and application thereof in the electroreduction of nitroaromatic hydrocarbons to arylamines. Background Art

[0002] Aromatic amines are used to make dyes, pharmaceuticals, resins and intermediates. They are one of the most produced chemicals in the world, with an output of approximately 7.85 million metric tons in 2023 (aniline). The synthesis of traditional industrial aromatic amines is generally carried out by chemical reduction and catalytic hydrogenation to reduce nitroaromatic hydrocarbons. The traditional chemical reduction method uses metal reducing agents (such as iron, zinc or tin). The process requires the addition of a large amount of metal, resulting in high reaction costs. At the same time, the reaction will generate a large amount of sludge, which is extremely polluting. The catalytic hydrogenation method uses precious metal catalysts and strong reducing agents (such as N 2 H 4 , NaBH 4 , CO or H 2 ) is carried out at high temperature and pressure, the process has low reaction efficiency, high carbon dioxide emissions, and the use of hydrogen leads to potential explosion risks. Therefore, we urgently need a more efficient strategy driven by renewable energy to meet production requirements in terms of sustainability and chemical compatibility.

[0003] Electrochemical-based selective reduction is a compelling alternative to the conventional reduction of nitrobenzene to aniline, as it can produce the desired chemicals using renewable electricity. Its unique advantages include mild reaction conditions, excellent energy efficiency, and the use of water as a green hydrogen source. Although electrocatalytic nitroaromatic reduction has been extensively studied and has achieved promising results, it is still difficult to achieve stable reaction (<200 h), slow reaction rate (current density <100 mA-cm -2 ), low tolerance to reaction conditions (potential or pH value) and poor matrix extensibility have seriously restricted its application in industry. In addition, the current catalyst system for catalyzing nitrobenzene to prepare aniline rarely considers the production efficiency and practicality of actual applications. The main research direction is focused on improving the performance of one-pot reactions, without extending to the stability of the catalytic system, the amplification of reactions and the extensibility of reactions of various nitro compounds. Summary of the invention

[0004] Purpose of the invention: The technical problem to be solved by the present invention is to provide a self-supporting ruthenium-copper alloy nanomaterial and its application in the electrocatalytic preparation of amino compounds in view of the deficiencies in the prior art.

[0005] In order to solve the above technical problems, the present invention discloses a self-supporting ruthenium-copper alloy nanomaterial, which is prepared by the following steps: placing the foamed copper washed with hydrochloric acid in a persulfate and alkaline solution for 0.5 to 2 hours, then washing it with deionized water, and soaking it in a ruthenium chloride solution. After washing, the temperature is raised to 100 to 300° C. under the protection of inert gas, maintained for 0.5 to 4 hours, then cooled to room temperature, and finally in an alkaline solution at -50 to -500 mA·cm -2 The current density is restored for 2 to 6 hours.

[0006] Wherein, the foam copper is cleaned with hydrochloric acid.

[0007] The persulfate is any one of ammonium persulfate, potassium persulfate or sodium persulfate, and the concentration is 0.05-0.5M; the alkaline solution is potassium hydroxide or sodium hydroxide, and the concentration is 0.1-2M.

[0008] Preferably, the persulfate is ammonium persulfate with a concentration of 0.1 M, and the alkaline solution is potassium hydroxide with a concentration of 1 M.

[0009] The concentration of the ruthenium chloride solution is 0.05-0.5 mM, and the soaking time is 2-20 hours.

[0010] The alkaline solution is 0.1M-2M KOH or NaOH solution.

[0011] The inert gas is nitrogen or argon.

[0012] Preferably, the heating rate is 5-20°C / min.

[0013] The present invention further proposes the application of the self-supporting ruthenium-copper alloy nanomaterial in the electrocatalytic preparation of amino compounds from nitro compounds.

[0014] Specifically, when used, the reaction conditions are an aqueous solution with a pH of 0 to 14, a reaction substrate concentration of 0.01 to 0.25 M, a reaction voltage range of 0 to -0.7 V, and a reaction pH of 0 to 1.

[0015] Beneficial effects: This application uses an ultrafast and simple ion exchange method to synthesize a self-supporting RuCu catalyst (named RuCu NSs), which can efficiently electroreducing nitroaromatics to aromatic amines. Using p-nitrophenol as a model substrate, RuCu alloy can achieve ultrahigh yield (>99.9%), Faradaic efficiency (>99.9%) and selectivity (>99.9%) in a wide potential range. In a wide pH solution range (including 1M KOH, 0.5M KOH, 0.6M KOH, 0.7M KOH, 0.8M KOH, 0.9M KOH, 1.3M KOH, 2.5M KOH, 3.5M KOH, 4.5M KOH, 5.5M KOH, 6.5M KOH, 7.5M KOH, 8.5M KOH, 9.5M KOH, 1.3M KOH, 2.5M KOH, 2 SO 4 and 0.5MH 2 SO 4) and a wide range of p-nitrophenol concentrations (12.5-250mM), showing good application potential. At the same time, in a scaled-up flow electrochemical reactor, high performance was still maintained when the cell voltage was only 2.5V (current was -1.38A), and it could operate stably for 1,060 hours to obtain kilogram-level products (0.501 kg of p-aminophenol). In addition, the same electrocatalytic strategy seems to be effective for various nitroaromatics. In summary, the universal reduction of nitroaromatics was successfully achieved using electricity as a renewable energy source and water as a green hydrogen source, paving the way for safer, more sustainable and more economical chemical / material manufacturing. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 Schematic diagram of the synthesis steps of RuCu NSs;

[0017] Figure 2 XRD patterns of copper foam, Cu NSs and RuCu NSs;

[0018] Figure 3 High-resolution transmission electron microscopy lattice diffraction patterns of Cu NSs and RuCu NSs;

[0019] Figure 4 Transmission electron microscopy images of Cu NSs (1) and RuCu NSs (2);

[0020] Figure 5 Atomic force microscopy images of Cu NSs (1) and RuCu NSs (2);

[0021] Figure 6 The left figure shows the Cu 2p XPS images of Cu NSs and RuCu NSs, and the right figure shows the Ru 3d XPS images of RuCu NSs and RuCuO;

[0022] Figure 7 Linear sweep voltammetry and constant potential electrolysis tests were performed for Cu NSs and RuCu NSs in 1 M KOH solution;

[0023] Figure 8 For Cu NSs and RuCu NSs at 0.5 MK 2 SO 4 Linear sweep voltammetry test and constant potential electrolysis test in solution;

[0024] Fig. 9 For Cu NSs and RuCu NSs at 0.5MH 2 SO 4 Linear sweep voltammetry test and constant potential electrolysis test in solution;

[0025] Fig.10 is the partial current density obtained according to LSV and constant potential electrolysis;

[0026] Fig.11 is the p-nitrophenol reduction performance of RuCu NS / CF on p-nitrophenol at different concentrations;

[0027] Fig.12 Polarization curve of RuCu NSs for the reduction of p-nitrophenol in a flow electrolytic cell;

[0028] Fig.13 The long-term electrocatalytic stability of RuCu NS / CF was tested under the condition of Ecell = 2.5 V using a continuous flow system (125 mM p-nitrophenol + 1 M KOH);

[0029] Fig.14 The results of the performance tests of RuCu NSs in a flow reactor and a primary reaction are presented, and the stability and Faradaic efficiency are compared with other works;

[0030] Fig.15 The catalytic effects of RuCu NSs on various types of nitroaromatics as substrate molecules. DETAILED DESCRIPTION

[0031] The present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments, and the above and / or other advantages of the present invention will become more clear.

[0032] Example 1 Preparation of self-supported RuCu catalyst (RuCu NSs).

[0033] Figure 1 The synthesis diagram of RuCu catalyst is shown in Figure 2. The copper foam washed with hydrochloric acid was placed in 0.1M ammonium persulfate and 1M potassium hydroxide solution and soaked for 1 hour, then washed with deionized water and placed in 10mM ruthenium chloride solution and soaked for 12 hours. After washing, the temperature was raised to 200℃ at a rate of 10℃ / min under nitrogen protection, maintained for 2h, and then cooled to room temperature. Finally, the copper foam was placed in 1M KOH solution at -100mA·cm -2 The RuCu NSs were obtained by reduction at a current density of 1.000 Å for 6 h.

[0034] Meanwhile, a catalyst control sample without Ru was prepared in the same manner, with the treatment method being similar to that described above, except that the ruthenium chloride solution was replaced with a pure aqueous solution to obtain Cu NSs.

[0035] Figure 2 to Figure 6The figure is a characterization result of the synthesized RuCu NSs. This application adopts an ultrafast and simple ion exchange method to synthesize a self-supporting RuCu catalyst. The strategy not only allows large-scale and simple synthesis of the catalyst, but also has a short synthesis time and has the potential for large-scale production. The crystal structures of RuCu NSs and Cu NSs were determined by X-ray diffraction (XRD) and high-resolution transmission electron microscopy (HRTEM).

[0036] like Figure 2 As shown in Figure 2, Cu NSs and RuCu NSs show the characteristic diffraction peaks of tetragonal Cu (PDF NO. 1). The interplanar spacing of RuCu NSs measured by HRTEM is 0.207 nm ( Figure 3 ), which corresponds to the (111) plane of Cu. Low-magnification transmission electron microscopy (TEM) can further observe the RuCu nanosheet structure ( Figure 4 ),in Figure 4 (1) is Cu NSs, and (2) is RuCuNSs. The atomic force microscopy (AFM) images of RuCu NSs further show that the thickness of the nanosheets is about 80 nm ( Figure 5 ).

[0037] The electronic structures of RuCu NSs and Cu NSs were studied by XPS. In the high-resolution Cu 2p2 / 3 XPS spectrum of RuCu NSs, the 2p2 / 3 binding peaks at about 933.5eV, 935.1eV, and 942.5eV are attributed to Cu 2+ , Cu + / Cu 0 and satellite peaks. Compared with Cu NSs, the binding energy of Cu in RuCu NSs is reduced by 0.4 eV, which indicates that Ru doping reduces the valence state of Cu. After electrochemical reduction, the Ru 3d5 / 2 characteristic peak of Ru decreases from 281.3 eV to 280.5 eV, and Ru exists in the form of Ru0 ( Figure 6 ). In summary, we have successfully synthesized RuCu alloy nanosheets on copper foam substrate.

[0038] Example 2 Application of RuCu alloy nanosheets in the electrocatalytic preparation of amino compounds.

[0039] p-Aminophenol is a widely used fine organic chemical intermediate. For the model reaction of p-nitrophenol (p-NP) to p-aminophenol (p-AP), the linear sweep voltammetry (LSV) method was first used to systematically evaluate the performance of RuCu NSs and Cu NSs in 1 M KOH, 0.5 M KOH, and 1 M KOH. 2 SO 4 and 0.5MH 2 SO 4The p-nitrophenol reduction performance in Figure 7-Figure 9 . The hydrogen evolution reaction (HER) performance in various solutions was significantly improved after the incorporation of Ru. After the addition of 25 mM p-NP, the reduction current in all solutions increased, indicating that the p-NP was effectively reduced, and the reduction current of RuCu to p-NP increased significantly compared to Cu as the pH value decreased. The electrocatalytic p-NP reduction performance of RuCu NSs and Cu NSs in different solutions was further studied under different potential conditions. Specifically, during the electrolysis process, the amount of electricity required for the theoretical complete conversion of the substrate (579.9C, the yield is numerically equal to the Faraday efficiency) was injected at different potentials, and the products were quantified by high-performance liquid chromatography (HPLC). Figures 7 to 9 As shown. In 1M KOH, the onset potential of RuCu NSs is 0.4 V RHE , the yield, FE, and selectivity of the reaction remained at around 99% between 0.1 V and -0.3 V, which was significantly higher than that of Cu NSs. Similar to alkaline solutions, RuCu NSs had a higher onset potential and higher reducibility at low potentials compared with Cu NSs. In conclusion, RuCu NSs can reduce p-nitrophenol to p-aminophenol in a wide potential range in solutions with different pH values.

[0040] In order to further compare the reaction characteristics, partial current densities were calculated. Fig.10 As shown, the alkaline solution has the highest current density, followed by the acidic and neutral solutions.

[0041] To further investigate the potential for industrial production, we conducted a series of experiments on RuCu NSs.

[0042] The reaction conditions were: 1M KOH solution (40 mL), an electrode area of ​​4 cm 2 The prepared RuCu electrode was used as the working electrode, the Pt sheet was used as the counter electrode, and the mercuric oxide was used as the reference electrode. The reaction potential was 0 V relative to RHE, and the amount of electricity passed per 1 mmol of substrate was 580 C. The results showed that the prepared RuCu catalyst can maintain high performance in a wide range ( Fig.11 ).

[0043] Long-term stability at high current density is a prerequisite for application. RuCu NSs were tested in a flow reactor. The reaction conditions were: 100 mM p-nitrophenol in 1 M KOH solution (400 mL) and an electrode area of ​​4 cm 2 The prepared RuCu electrode was used as the working electrode, the RuIr titanium mesh was used as the counter electrode, the reaction potential was 0V relative to RHE, and the amount of electricity passed per 1mmol of substrate was 600C. After the reaction was complete, a new solution was replaced to continue the reaction. Fig.12 As shown, the polarization curve shows that the potential of 1.11Vcell starts to drive the reaction. At the electrolysis voltage of 2.5V, the total current is -1.38A and the current density is -0.34A. The electrolysis voltage can be reduced by further optimizing the structure of the electrolysis device (such as using a membrane electrode, or increasing the temperature) and replacing the anode oxygen evolution reaction (such as various types of alcohol oxidation). After 1060 hours of constant potential polarization, the current density of RuCu remains stable ( Fig.13 ), the Faradaic efficiency remained at 90%, the selectivity remained at 94%, and 0.511 kg of crude p-aminophenol was obtained. Compared with previously reported catalysts, both single-cell reactions and 1060 hours of flow electrolysis showed strong competitiveness ( Fig.14 and Table 1). This further confirms the excellent effect of electrocatalysis in practical applications.

[0044] Table 1

[0045]

[0046]

[0047] Furthermore, in order to study the substrate scope of RuCu NSs, we used various types of nitroaromatics as substrate molecules, using the prepared RuCu NSs as the cathode, platinum sheet as the anode, adding 1 mmol of reactants, and the reaction solution was 35 mL of 1 M KOH solution and 5 mL of dioxane (to increase the solubility of the substrate), as shown in Fig.15 As shown. RuCu NSs have high yields and selectivities for common electron-withdrawing and electron-donating groups (2b-2g), and can also maintain good performance for molecules containing other easily reducible groups (2h-2o) such as halogens, carbon-carbon double bonds, and carbon-carbon triple bonds, as well as non-aromatic nitrobenzenes (2s), nitrobenzenes containing N-heterocyclic groups (2t), and nitrobenzenes containing multiple nitro groups (2u). Nitrobenzene aromatic compounds (2p-2r) containing groups that are unstable in acid and alkaline solutions (such as cyano, carbonyl, and aldehyde groups) are still highly active because RuCu NSs can function in solutions with a wide range of pH values. For drugs (2x, 2y) and drug derivatives (2v, 2w), RuCu NSs can ensure the stability of functional groups in substrate molecules.

[0048] The present invention provides a self-supporting ruthenium copper alloy nanomaterial and its application in the electrocatalytic preparation of amino compounds. There are many methods and ways to implement the technical solution. The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the protection scope of the present invention. All components not specified in this embodiment can be implemented by existing technologies.

Claims

1. A self-supporting ruthenium-copper alloy nanomaterial, characterized in that: The method is prepared by the following steps: placing the copper foam washed with hydrochloric acid in a persulfate and alkaline solution for 0.5 to 2 hours, then washing it with deionized water, and then soaking it in a ruthenium chloride solution. After washing, the temperature is raised to 100 to 300 ° C under the protection of inert gas, maintained for 0.5 to 4 hours, then cooled to room temperature, and finally heated in an alkaline solution at -50 to -500 mA•cm -2 The current density is restored for 2 to 6 hours.

2. The self-supporting ruthenium-copper alloy nanomaterial according to claim 1, characterized in that: The foam copper is cleaned with hydrochloric acid.

3. The self-supporting ruthenium-copper alloy nanomaterial according to claim 1, characterized in that: The persulfate is any one of ammonium persulfate, potassium persulfate or sodium persulfate, and the concentration is 0.05~0.5 M; The alkaline solution is potassium hydroxide or sodium hydroxide, and the concentration is 0.1-2 M.

4. The self-supporting ruthenium-copper alloy nanomaterial according to claim 1, characterized in that: The persulfate is ammonium persulfate with a concentration of 0.1 M, and the alkaline solution is potassium hydroxide with a concentration of 1 M.

5. The self-supporting ruthenium-copper alloy nanomaterial according to claim 1, characterized in that: The concentration of the ruthenium chloride solution is 0.05-0.5 mM, and the immersion time is 2-20 h.

6. The self-supporting ruthenium-copper alloy nanomaterial according to claim 1, characterized in that: The alkaline solution is 0.1 M~2 M KOH or NaOH solution.

7. The self-supporting ruthenium-copper alloy nanomaterial according to claim 1, characterized in that: The inert gas is nitrogen or argon.

8. The self-supporting ruthenium-copper alloy nanomaterial according to claim 1, characterized in that: The heating rate is 5-20℃ / min.

9. Use of the self-supporting ruthenium-copper alloy nanomaterial according to any one of claims 1 to 8 in the electrocatalytic preparation of amino compounds from nitro compounds.

10. The use according to claim 9, characterized in that: The reaction conditions are an aqueous solution with a pH of 0 to 14, a reaction substrate concentration of 0.01 to 0.25 M, a reaction voltage range of 0 to -0.7 V, and a reaction pH of 0 to 1.

Citation Information

Patent Citations

  • Preparation method and application of self-supporting copper selenide nanosheet electrocatalyst

    CN116043258A

  • Multimetallic catalyst and process for preparing substituted aromatic amines

    DE19636214A1